2016
DOI: 10.1111/jgh.13081
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in tissue acquisition in malignant pancreatic neoplasms

Abstract: Although EUS-FNA is increasingly performed and is less costly, and the rate of surgical biopsies has declined precipitously, the utilization of percutaneous techniques remains prevalent. Training and education are required to disseminate the use of EUS-FNA outside major teaching institutions or foster referral of patients to EUS centers because of implications for patient care and resource use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Although EUS‐FNA is the current modality of choice for tissue acquisition in patients with pancreatic mass lesions, reliable procurement of histological tissue remains a challenge. Given the technical limitations associated with the use of Tru‐cut biopsy needles and the lack of difference between the ProCore and standard FNA needles a novel fork‐tip biopsy needle (SharkCore; Medtronic Inc., Boston, MA, USA) was recently developed to procure histology samples.…”
Section: Discussionmentioning
confidence: 99%
“…Although EUS‐FNA is the current modality of choice for tissue acquisition in patients with pancreatic mass lesions, reliable procurement of histological tissue remains a challenge. Given the technical limitations associated with the use of Tru‐cut biopsy needles and the lack of difference between the ProCore and standard FNA needles a novel fork‐tip biopsy needle (SharkCore; Medtronic Inc., Boston, MA, USA) was recently developed to procure histology samples.…”
Section: Discussionmentioning
confidence: 99%
“…A 5-year retrospective claims analysis of Medicare patients undergoing sampling of pancreatic malignancies showed an ongoing trend towards EUS-guided sampling. However, in spite of higher costs, the application of percutaneous image-guided sampling remained prevalent in particular outside major academic and urban hospitals [195].…”
Section: Eus-guided Sampling: Indications and Clinical Impact !mentioning
confidence: 99%
“…The use of FNA biopsy in the management of pancreatic tumors has been well established. Whereas pancreatic FNA routinely applies CS for diagnosis, previous studies have shown that the diagnostic performance of pancreatic FNA partly depends on the rapid assessment provided by cytologists [2][3][4][5][6]. ROSE ensures the effectiveness of biopsy and avoids inadequate sampling.…”
Section: Introductionmentioning
confidence: 99%
“…Such issues could be easily overcome by the use of ROSE. ROSE helps to evaluate on-site sampling, decrease inadequate samples and improve the diagnostic rate by 10-30%[2][3][4][5][6]. However, due to labor and time requirements, ROSE is hardly used.…”
mentioning
confidence: 99%